2013
DOI: 10.1159/000353418
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with Mineral Metabolism Targets in Haemodialysis Patients: Moving Backwards?

Abstract: Background: To standardize therapy and improve the clinical outcome for chronic haemodialysis (HD) patients, guidelines have been developed for mineral metabolism management. We evaluated compliance with different mineral metabolism guidelines. Methods: 2,951 chronic HD patients from 61 dialysis centres in Spain were studied. Mineral metabolism management data from a 1-year period were analysed according to KDOQI, KDIGO, and Spanish guidelines. Results: Only 1% (KDOQI), 6% (KDIGO) and 11% (Spanish guidelines) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…This study found that PTH was positively associated with dialysis vintage ( Fig 3 and Table 3 ); this is not an unusual finding since there are reports showing that hyperparathyroidism progresses with time on dialysis until the patient becomes older. Age, is known to be negatively associated with PTH and with a tendency to adynamic bone disease [ 10 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study found that PTH was positively associated with dialysis vintage ( Fig 3 and Table 3 ); this is not an unusual finding since there are reports showing that hyperparathyroidism progresses with time on dialysis until the patient becomes older. Age, is known to be negatively associated with PTH and with a tendency to adynamic bone disease [ 10 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to the recommended target ranges slightly increased after dialysis onset, but nearly 85% of the patients failed to attain the three main KDIGO targets 2 years later. However, compliance with MBD targets seems higher in France than in Spain, where only 6% of the patients consistently achieved the three main KDIGO targets over a 1-year follow-up period [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current issue, Palomares et al [1] lament the poor compliance with various guideline targets for mineral metabolism in hemodialysis patients. I suggest this is welcome news.…”
Section: Figmentioning
confidence: 99%